Teacher Preparedness in Implementing Inclusive Education for Pupils with Hearing Impairments in Mombasa County, Kenya - Luvanga, Mr. Hassan; Mwangi, Dr. Sarah W.; Maneno, Dr. Robert J. (International Journal of Scientific Research and Management (IJSRM), 2020)
Inclusion is a philosophy that focuses on the process of adjusting the home, school and the larger society to accommodate persons with special needs. The success of provision of inclusive practices is contingent upon the quality of teaching in an inclusive setting. This study was conducted in Mombasa County, Kenya. The study investigated teacher preparedness in the implementation of special needs inclusive education in primary schools with pupils with hearing impairments. The study focused on teachers’ academic qualifications, professional qualifications, teaching experience and whether the teachers had undertaken pre- service or in-service special education training. The prospective study was carried out between 2018- 2019 including 60 teachers and 20 head teachers. The findings revealed that although most teachers had the necessary academic qualifications to teach pupils in primary schools, they lacked adequate special education training to effectively teach pupils with hearing impairment and majority of the teachers had not undertaken any pre-service or in-service special education training to prepare them to effectively teach pupils with hearing impairments. Recommendations suggested that teachers should be adequately prepared during their pre-service education programme to effectively teach pupils with hearing impairments within the mainstream classroom setting. Recommendation was that teachers should enhance their special education skills through in-service special education training.